Long run impact of share buyback initiation toward the share price of firms listed in Kuala Lumpur stock exchange. - Chong, Chuan Wei (Universiti Malaysia Sarawak (UNIMAS), 2013)
This paper is attempted to investigate and evaluate the long run impact of share buyback initiation toward the share price of firms in Kuala Lumpur Stock Exchange. This research involves firms that initiated share buyback from the year of 1999 until 2008 in Kuala Lumpur Stock Exchange.The share price is recorded every month for three years after the first share buyback is carried out. The recorded share price will later be calculated with formula of Buy-and-Hold, BHR and Buy-and-Hold Abnormal Return, BHAR by using Kuala Lumpur Composite Index as the benchmark. T -statistic value is computed manually to show the existence of BHAR value. The t-statistic value computed showed that BHAR value is not equal to zero. After that, BHAR value is regressed with book-to-market ratio and market value of the firm. After carry out the regression, the conclusion found that both Book-to-Market and Market Value show relationship with share price.